AN ANALISIS OF THE ATRIBUTION OF PERSONAL PERSPECTIVES IN METAFICTION - Brugnami, Enrico (Analysis. Journal of Philosophical Research, 2024)
This article analyses the role of personal perspectives in the metafictional works Six Characters in Search of an Author by Luigi Pirandello (1969) and Opus by Satoshi Kon (2021a, 2021b). To do so, it first examines the concept of personal perspective considering the work of Manuel Liz and Margarita Vázquez, as well as taking into account some criteria for attributing personal identity to subjects. Subsequently, the concept of metafiction is explored in comparison with that of fiction, explaining how Pirandello's and Kon's works qualify as metafictional. Particular attention is given to the interaction between the different ontological layers in both works, especially in Opus. Following this, the analysis focuses on which elements of the perspectives expressed by the characters can be considered personal aspects and how they differ from perspectives in more conventional works of fiction. Finally, the article reflects possibility and convenience of ascribing personal perspectives to fictional and metafictional characters.